Marketing: o nível de consciência ecológica do consumidor e o efeito Framig (enquadramento da mensagem) - Sacramento, Sônia Regina Valério do (2013)
According to the Ministério do Meio Ambiente (2013 ) , in 2020 hundred and seventeen million Brazilians will be part of the new Brazilian middle class , you must create standards Brazilian consumer in harmony with the environment , human health and society in general. Marketing , through its environmental aspects , has been proven effective for behavioral changes in humans . The level of environmental awareness of consumers has been little considered in the framework of the messages in the context of gain and loss to persuade the adoption of ecological behavior. To better understand the influence of the levels of consciousness ecology, the environment for messages in ecological behavior and construct persusão was conducted a literature and empirical research , to conducting an experiment . We interviewed 188 undergraduate students . The results confirm that consumers with high ecological awareness respond more positively to behavior intention of ecological consumption than consumers with low ecological consciousness when exposed to framing and gain when exposed to loss framing . Signaling that marketers should target your campaigns to consumers of low ecological awareness in order to increase the level of awareness of this population.